Numerical computations of next-to-leading order corrections in spinfoam large-j asymptotics - Han, Muxin; Huang, Zichang; Liu, Hongguang; Qu, Dongxue (Physical Review D, 2020)
We numerically study the next-to-leading order corrections of the Lorentzian Engle-Pereira-RovelliLivine (EPRL) 4-simplex amplitude in the large- j expansions. We perform large- j expansions of Lorentzian EPRL 4-simplex amplitudes with two different types of boundary states, the coherent intertwiners and the coherent spin-network, and numerically compute the leading-order and the next-to-leading order O(1/j) contributions of these amplitudes. We also study the dependences of these O(1/j) corrections on the Barbero-Inunirzi parameter gamma. We show that they, as functions of gamma, stabilize to finite real constants as gamma -> infinity. Lastly, we obtain the quantum corrections to the Regge action because of the O(1/j) contribution to the spinfoam amplitude.
CRIS-Team WoS Importer:2021-01-01